Resistance of cattle to the tick Boophilus microplus. II. Natural infestation - Oliveira, Gilson Pereira de; Alencar, Maurício Mello de; Freitas, Alfredo Ribeiro de (Pesquisa Agropecuaria Brasileira, 2014)
The resistance of the Canchim cattle to the cattle tick, as compared to the Nelore cattle, was evaluated through natural infestation. Sixty animals (30 males and 30 females), hall of each breed, averaging 19 months of age, in Andropogon gayanus pastures, were used. Twelve counts of female engorged ticks, 28 days apart, were performed on the left side of each animal. The counts (x) were transformed to Y = log10 (x + 1), and the mean of these, within each of the four seasons of the year, were found to represent the animal status in the analysis of variance. The results showed no significant effects of the breed x sex interaction on the number of ticks counted. Breed x season (P < 0.01) and sex x season (P < 0.05) interactions showed significant effects on the trait studied; however, the Canchim animals and the males of both breeds showed higher levels of infestation in all seasons of the year, except during the spring when males and females showed no differences (P > 0.05). Season of the year significantly (P < 0.01) affected the trait, and the levels of infestation were higher during the fall and winter. The females (Y = 0.533) were significantly (P < 0.01) more resistant than the males (Y = 1.052). The Canchim (Y = 0.975) animals showed significantly (P < 0.01) higher infestation than the Nelore (Y = 0.607) ones.